CHANGES IN THE INNOVATIVE ACTIVITY OF POLISH ENTERPRISES IN THE YEARS 2019-2021 - Rak, Anna (Management and Administration Journal, 2024)
The underlying objective of this paper is to identify the condition of and specify the changes in the innovative activity of Polish enterprises in the years 2019–2021. The first part of the article constitutes an overview of the definitions and types of innovation presented in the subject literature. The empirical part involves an analysis of the results of GUS (Statistics Poland) studies conducted for three periods of innovative activity of enterprises (2017-2019, 2018-2020, 2019-2021). The results of the carried-out analyses indicate an increase in the share of innovative enterprises in the total number of enterprises in Poland. In each size class of industrial and service enterprises, the implementation of process innovations dominated. In the analysed period, an increasing expenditure on innovative activities was observed, and the expenditure dynamics indicators were significantly higher in the entities conducting service activities. In the structure of financing innovative activities own funds played the most important role, regardless of the size of the enterprise and the type of the activity.